Table of Content - -, (Journal of medical and pharmaceutical sciences, 2023)
Table of Content:1. Environmental Radiation Dosimetry for school buildings, hospitals and health centers in Babil Governorate-Iraq using TL-techniqueDr. Abdalrahman Al-Salihi , Dr. Riyadh Ch. Abul-Hail , Dr. Hussain A. Badran2. Study the effect of ketogenic diet on weight loss and lipid profile on obese ratsCo-Prof. Waheeba Elfaki Ahmed, Munirah Suliman Al-Meazil, Aseel Ali Al-Salamah3. Study of Suicidal Ideation and Attempt among HIV patients in Omdurman National Voluntary Counseling and Testing Centre Khartoum state - Sudan (2021-2022)Dr. Mohamed Almostafa Abd Aljwad Dahab Khalil, Dr. Aisha Motwakil Bakhiet Gailani4. The Experiences of Primary Healthcare Nurses During Covid-19 pandemic: Voices from Nursing Staff at King Fahad Specialist Hospital in BuraydahKhaled Falah Al-Rasheedi, Nasser Abdullah Al-Rasheedi, Fayez Shaman Al-Rasheedi, Muhammad Saleh Al-Mansour, Mufleh Ali Al-Harbi5. Renin-Angiotensin System Inhibition Improves Lipid Profile in Patients with Chronic Kidney DiseaseMrs. Ola Zarreif Salamah ,Dr. Afraa Zrieki , Prof. Hussein Said6. Providing pharmacy services during the coronavirus pandemic in Saudi Arabia (Review)Saad Khalaf Alshammari, Ahmed Masoud Alqahtani , Ahmed Mazi Alotaibi , Naif Ahmad Alzahrani , Emad Ahmed Alzahrani , Susan Abdulqader Alkhulaif , Waleed Farah Alharbi , Salem Ahmad Albraiki , Awad Ghalab Almuteiri , Nawaf Ateya Alzahrani7. The Experience of Newly Diagnosed Women with Breast Cancer in OmanZalikha Khamis Darwish Al-Marzouqi, Nawal Said Salim Al-Suraihi, Aida Said Bakeet Al-Dhoani
Keywords: Journal of Medical and Pharmaceutical Sciences